Financial Distress Analysis Using Altman Z-Score, Ohlson, And Fulmer Methods : Empirical Study Of Aviation Sector Companies Listed On The Idx In The Period Of 2018 To 2021 - Nurjanah, Yayuk; Darmawan, Ade (Institut Bisnis dan Informatika Kesatuan, 2024)
Financial Distress is a condition where a company is unable to meet its current obligations that have matured such as trade debts, short-term bank debts, tax debts, etc. Usually, companies that are indicated to be experiencing financial distress have minimal income, causing the company to be unable to finance its operational costs, therefore, supervision of the financial condition, both from the balance sheet and profit and loss reports, must be carried out by the company to minimize the potential for bankruptcy in the company.The purpose of compiling this thesis is to find out how the Financial Distress analysis is in Indonesian aviation sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 to 2021 using the Altman Z-Score, Ohlson, and Fulmer methods. This study uses secondary data on the companies PT. Air Asia Indonesia Tbk, PT. Garuda Indonesia Tbk, and PT. Jaya Trishindo Tbk with quantitative descriptive analysis techniques.The final results of this study indicate that there are 2 Indonesian Aviation Sector companies that experienced Financial Distress from 2018 to 2021 which were calculated using the Altman Z-Score and Fulmer methods. There is one company, namely PT. Jaya Trishindo Tbk which has no potential to experience Financial Distress in 2019 and 201, but has the potential to experience Financial Distress in 2018 and 2020 calculated using the Altman Z-Score method. And the three companies did not experience Financial Distress when calculated using the Ohlson method. Keywords : Financial Distress , Altman Z- Score , Ohlson, and Fulmer.